Trabalho, desenvolvimento e ação sindical em Pernambuco: o Sindmetal-PE diante do polo naval e do polo automotivo - Rodrigues, Victor de Oliveira (2020)
In the 1980s, while USA and Europe went through discussions on the crisis of unionism, Brazilian union movement was experiencing one of its most effervescent phases, starring strikes and massive mobilizations with the emergence of the new unionism, which began in the ABC region. from São Paulo and expanded to other regions of the country, questioning the official union structure, challenging the patronage and the dictatorial government. In Pernambuco, metallurgists were among the most active categories, with union opposition, represented on the party Zé Ferrugem, wich, in 1981, won the election for Metallurgical Workers Union (SindMetal-PE). However, in the following decade, economic opening, privatizations and new forms of work management have created obstacles to union action, creating a crisis in Brazilian unionism. In 2003, the election of Lula, a former union leader, for the presidency represented a shift in neoliberal orthodoxy and the expansion of interlocution with the union movement. Symbols of the new developmentalist perspective adopted in Brazil, the emergence of the naval pole of Suape, in 2008, and of the automotive pole of Goiana, in 2015, in Pernambuco, brought challenges to union’s performance and organization. This context was taken as object of study in this research, that aimed to analyze some of the main changes that Brazilian unionism has undergone, taking the specific case of SindMetal-PE, evaluating the limits and the possibilities of this union action. The methodological repertoire included the analysis of data from the Annual List of Social Information (RAIS), materials produced by the union, application of a questionnaire and interviews with workers and union board members. From context and resources of the union power analysis, it was observed a gap between the new contingent of metallurgical workers and the action of SindMetal-PE, causing the union difficulties to place itself as true representative of the category. In addition, with the partial reconstitution and analysis of the trajectories of two generations of union members, fundamental changes were found in the forms of agency and recruitment of new leaders, which caused the union to attract a new profile of directors, more featured by routine performance than by militant engagement, leading to limitations in the entity's performance repertoire.